Disaster victim identification in the 21st century : a US perspective - Williams, John A. (Physical anthropologist); Weedn, Victor Walter; John Wiley & Sons (Chichester, West Sussex : John Wiley & Sons Ltd, 2022)
'Mass fatality disasters, both natural and man-made are increasing in frequency. Extreme environmental disruptions like hurricanes, wildfires, and flooding are on the rise and in the news almost daily. Mass casualty terrorism is sadly also becoming more commonplace. In spite of improvements in technology common carrier crashes continue to take place. The COVID-19 pandemic has shown us that 21st century medicine can be outmatched by a'novel' virus that does not respect national boundaries. The deaths that result from these events place a different set of needs and obligations on those charged with disaster victim identification or DVI. In the United States during the 1980s the National Funeral Directors Association noticed with concern that there was no national coordinating body with regard to mass fatality events and DVI. The NFDA was the first organization to draw up plans for the handling of mass fatality victims. From their initial efforts came the Federal agency DMORT (Disaster Mortuary Operational Response Team) and the concept of a disaster morgue, marking the beginning of DVI in the United States as it is known today. Disaster Victim Identification is the comprehensive process of human identification as applied to mass fatality events. Although by definition a mass fatality event is any situation that overwhelms local resources, we generally think of situations in which identification is hampered by the event itself and the process of recovery from the event. Human remains that have been badly traumatized, heavily decomposed, or recovered outside of their normal context are examples that would require DVI'--
Introduction / John Williams and Victor Weedn -- Historical Background / Victor Weedn -- Quality Assurance in Disaster Victim Identification: The Case for Standards / Jason Wiersema and Michal Pierce -- Medicolegal Jurisdiction and Public and Private Agencies / John Williams and Jason Wiersema -- The DVI Morgue / John Williams -- Dentition and DVI / Kenneth Aschheim -- Fingerprints and DVI / Bryan Johnson -- DNA and Technology: The Future of DVI / Mark Wadhams and Taylor Dickerson -- The Victim Information Center and Data Collection: its Evolving Role in DVI / Jason Byrd -- Ethical and Legal Considerations in DVI / Victor Weedn -- DVI in the Changing 21st Century / Cynthia Gavin.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on May 03, 2022).
Added to collection customer.56279.3
Keywords: Disaster victims -- Identification; Dead -- Identification; Disaster Victims; Victimes de catastrophes -- Identification; Morts -- Identification; Dead -- Identification; Electronic books